URGENSI WIRAUSAHA DI LEMBAGA PENDIDIKAN - Amin Khizbullah, Muhammad; Mushthofa, Ahmad (Jurnal Tawadhu, 2021)
Education is the main means in developing human resources, the quality of a nation depends on the quality of its education, educational institutions are institutions that are responsible for the educational process, in improving the quality of education, managers must have sources of funds reliable and not only depend on the government and students, building entrepreneurship is one solution that can be done. The researcher uses a qualitative approach in his research, and uses the documentation method in collecting data. The purpose of this study is to examine the importance of educational institutions to have entrepreneurship. In his research, the authors found that having entrepreneurial educational institutions can improve the welfare of their educators and educational staff, in addition to having entrepreneurial educational institutions can also finance the ongoing process of education such as in the procurement of facilities and infrastructure and activities to improve the quality of educators and staff. education.